Peak VO2 during handcycling in spinal cord injured athletes: incremental versus verification testing - Rosa C. A.; Antunes D.; Ventura T. P.; Fischer G.; Brickley G.; Dantas de Lucas R.; Turnes T. (Applied Physiology, Nutrition, and Metabolism, 2025)
The present study aimed to compare peak oxygen uptake (VO2peak), peak heart rate (HRpeak), and peak O2pulse during an incremental and a verification test performed on the same day in hand-cyclists with spinal cord injury (SCI). Eight competitive SCI hand-cyclists (age: 23 ± 2.7 years; VO2peak: 36.3 ± 14.0 mL.kg-1.min-1) performed a maximal incremental handcycling test and a verification test to exhaustion at 100% of the peak speed on an oversized treadmill. The VO2peak, HRpeak, and peak O2pulse (i.e., VO2/HR) were compared between incremental and verification tests. Absolute and relative VO2peak obtained in the verification test (2.51 ± 0.96 L.min-1; 36.3 ± 14.0 mL.kg.min-1) were significantly higher than values obtained in the incremental test (2.24 ± 0.79 L.min-1; 33.5 ± 12.9 mL.kg.min-1; P < 0.05). The mean differences (95% CL) of absolute and relative VO2peak between tests were 8.2% (3.3%-13.2%) and 10.9% (4.3%-18.1%), respectively. There was no difference in HR peak (incremental: 169 ± 24 bpm; verification 167 ± 25 bpm; P = 0.130). Peak O2pulse from the verification test (14.6 ± 4.7 mL.beat-1) was higher than incremental test (13.0 ± 3.8 mL.beat-1; P = 0.007). In conclusion, the verification test elicited greater VO2peak and O2pulse than a two-phase incremental test despite the similar HRpeak. This indicates that for this progressive protocol lasting =25 min, the verification phase adds value to determining VO2peak in SCI athletes.